Penguatan Kelembagaan Kelurahan Pasca Implementasi UU No. 23 Tahun 2014 tentang Pemerintahan Daerah - Bambang Tri Harsanto; Slamet Rosyadi; Wahyuningrat Wahyuningrat; Simin Simin (Faculty of Social and Political Science, Universitas Airlangga, 2017)
The reduction of kelurahan (Sub-District Government) authority has decreased its duties and functions after the implementation of the Law No. 23/2014 on Local Governance. This policy stimulates several kelurahan at Wonosobo Region to propose their villages’ status changing from kelurahan into desa (Rural Government). Based on this case, this research aims to analyze the actual performance of kelurahan, and the motives of the village status changing. This research uses descriptive qualitative approach to answer those objectives.Observation, in-depth interview and focus group discussion are used to obtain data from informants who represent kelurahan, local government, non-government organizations and community leaders. Technique ofdata analysis of this research uses interactive data analysis including collecting, condensing, and describing data which is ended by conclusion. Results of study show that although the main function and tasks of kelurahan has decreased significantly, in general, the performance in service area still satisfies the public. However, services for development of public facilities are still far from public expectation. Furthermore, this research also found that there are 4 aspects encouraging the kelurahan to change into desa, namely economic, political, geographical and community profile motives. Implication of this research leads to the need of strengthening of kelurahan particularly in developing physical facilities provision service. It is intended to anticipate the possibility of kelurahan which will be left behind by desa.